Mesial Temporal Lobe Epilepsy: Role of Reelin Signalling Pathway. (1st September 2019) - Gupta, Tulika; Kaur, Mandeep; Singla, Navneet; Radotra, Bishan; Gupta, Sunil K; Sahni, Daisy
Abstract: INTRODUCTION: Granule cell dispersion (GCD) is pathognomonic of hippocampal sclerosis seen in mesial temporal lobe epilepsy (MTLE). Current animal studies associate GCD to deficiency of Reelin, an extracellular matrix protein. The present study evaluated complete Reelin signalling pathway in MTLE in human tissue hippocampus and anterior temporal lobe (ATL). ATL was included, as ATL resection along with amygdalo-hippocampectomy results in better disease control. METHODS: Hematoxylin and Eosin (H&E) staining was done to identify the MTLE. Gene expression profiles of Reelin and its receptors (very low density lipoprotein-VLDLR and Apolipoprotein E 2-ApoER2), its downstream molecule Disabled 1 (Dab1) and its upstream inhibitor tissue inhibitor of metalloproteinases-1 (TIMP-1) were compared in normal and epileptic human tissue. Quantitative real-time PCR was done to determine the gene expression in the hippocampus and ATL. Western blotting was done to quantify the protein expression. Ethical clearance was taken from the Institute Ethical committee. RESULTS: Typical features of MTLE were seen histologically. Width of granule cell layer was found to be broadened than normal controls. The expression of Reelin was found to be in same order to that of control. But its expression has been reduced as compared to the other genes. Reactive increase in the expression of both receptors was found. In hippocampus increase was more for ApoER2 while in ATL VLDLR showed increased expression. Similarly increased expression of Dab1 was seen, more in the hippocampus. Significantly increased expression was found in TIMP-1. CONCLUSION: Data suggests a causative role of Reelin deficiency in MTLE. The increase in TIMP-1 would inhibit the Reelin cleavage, leading to deficiency of active Reelin. Downstream components of the Reelin show reactive increase. Reelin deficiency in ATL validates the surgical significance of ATL resection. Establishing a causative role of Reelin in MTLE in human tissue might have significant therapeutic potential.